Critiquing Mental Accounting in Self-Reward Behavior: Toward Falah-Oriented Self-Reward - Lingga Sekar Arum; Krisno Septyan (Al-Infaq Jurnal Ekonomi Islam, 2026)
This study explores the influence of mental accounting on self-reward behavior and shifts its ultimate orientation toward falah. This research fills the gap in private accounting by applying noble Islamic values. Using the tazkiyah al-nafs method, the research is conducted through stages of recognizing the intrinsic sin of self-reward, acknowledging Allah as the highest stakeholder, and transforming self-reward into worship rather than self-indulgence. Findings show that mental accounting creates rationalization that blurs the boundaries between needs and wants. Cost-benefit thinking from conventional accounting has infiltrated private accounting, where individuals equate effort (cost) with material rewards (benefit), ignoring Allah's pleasure as the true reward. This research reinterprets self-reward as a form of worship to Allah, shifting from egocentrism toward actions that prioritize collective benefit (maslahah). By integrating gratitude and sufficiency, falah-oriented self-reward transcends worldly happiness to reach the hereafter. This study contributes to accounting discourse by bridging private finance with Islamic values, demonstrating that falah cannot be measured solely in numerical terms but must encompass spiritual and social dimensions.